Peripheral Immune Cells Exhaustion and Functional Impairment in Patients With Chronic Hepatitis B - Jin, Xin; Yan, Zhi-han; Lu, Lingna; Lu, Shengjia; Zhang, Guoping; Lin, Wei (Frontiers in Medicine, 2021)
After infection of hepatitis B virus (HBV), the virus induces a variety of immune disorders in the host, leading to immune escape and, finally, the chronicity of the disease. This study investigated immune cell defects and functional impairment in patients with chronic hepatitis B (CHB). We analyzed the percentage, function, and phenotypes of various immune cell subpopulations in the peripheral blood along with the concentrations of cytokines in the plasma. We compared the results between patients with CHB and healthy individuals. It was found that in patients with CHB, the cell function was impaired and, there was increased expression of inhibitory receptors, such as NKG2A and PD-1 in both NK and T cells. The impairment of function was mainly in cytokine secretion, and the cytotoxicity was not significantly diminished. We also found that the proportion of dendritic cells (DC) decreased and regulatory B cells (Breg) increased in CHB. In addition, the Breg cells were negatively correlated with T cell cytokine and positively correlated with ALT and HBV viral load. Taken together, various disorders and functional impairments were found in the immune cells of peripheral blood in CHB patients, especially NK and T cells. These cells showed exhaustion and the increase of regulatory B cells may be one of the reasons for this phenomenon.